Heterogeneous Photocatalytic Degradation for Treatment of Oil from Wastewater - Mustafa, Yasmin A.; Alwared, Abeer I.; Ebrahim, Mothana (Al-Khwarizmi Engineering Journal, 2014)
In the present study, advanced oxidation process / heterogeneous photocatalytic process (UV/TiO2/Fenton) system was investigated to the treatment of oily wastewater. The present study was conducted to evaluate the effect of hydrogen peroxide concentration H2O2, initial amount of the iron catalyst Fe+2, pH, temperature, amount of TiO2 and the concentration of oil in the wastewater.  The removal efficiency for the system UV/TiO2/Fenton at optimal conditions and dosage (H2O2 = 400mg/L, Fe+2 = 40mg/L, pH=5, temperature =30oC, TiO2=75mg/L) for 1000mg/L load was found to be 77%.Aluminum foil cover around the reactor and air bubbling were utilized in the experiments of photo Fenton UV/ H2O2/Fe+2 homogeneous and heterogeneous systems in order to improve the removal efficiency. The removal efficiency was improved to 81% for UV/TiO2/Fenton system . The reaction was found to be of a first order throughout the systems.